Knee Alignment in Adolescent Football Trainees - Itikap, Muhammad; Mughnie, Burlian (Journal of Prosthetics Orthotics and Science Technology, 2022)
Genu varum and valgum can trigger for osteoarthritis and happened between 16-18 years old. The study aimed to find out the relationship between knee joint alignment and footballers activities. This was a cross-sectional study, with 64 participants from two groups and only participants whom were meet all inclusion criteria were joined. It showed the knee joint angle in comparison to the norm was very significant with p- value 0.000 and there was a connection to practicing football against knee joint alignment, more specifically varum. In conclusion, there is a significant relationship between practicing football and the knee joint as measured by degree og genu varum and vagum as differences were found in year and duration of training.